Optimizing The Marketing of Private School Educational Services through Local Wisdom Approaches - Danurwendo, Yudha Suryanjaya; Sutama, S (Universitas Muhammadiyah Surakarta, 2025)
This study aims to examine strategies for optimizing the marketing of educational services in private schools through a local wisdom-based approach. Educational service marketing is one of the key factors determining the success of private schools in attracting public interest, increasing student enrollment, and sustaining their existence amid increasingly competitive conditions. However, most marketing strategies implemented thus far tend to rely primarily on modern approaches such as the use of social media, formal branding, and technology-based innovations, without adequately considering the potential of local cultural values within the school's environment. In fact, local wisdom can serve as a unique competitive advantage and as a distinctive identity of the school in the eyes of the community. This study employs a qualitative method with a literature review approach, conducted through the exploration and analysis of scholarly articles, books, and research reports published within the past five years (2020-2025). The findings reveal that integrating local wisdom values into school marketing strategies can strengthen the school's positive image, enhance public trust, and foster stronger emotional connections between schools and their surrounding communities. Local values promoted through school marketing, educational programs, and services are shown to be more easily accepted by the community, as they align with prevailing cultural norms. Therefore, private schools need to formulate marketing strategies that are not only adaptive to contemporary developments but also contextualized with the local wisdom of their surrounding communities. This study is expected to provide theoretical contributions to the development of educational management literature as well as practical references for school administrators in designing relevant and effective marketing strategies.